Effects of microvoids on strength of unidirectional fiber-reinforced composite materials. (15th April 2020) - Hyde, Alden; He, Jinlong; Cui, Xiaodong; Lua, Jim; Liu, Ling
Abstract: Microvoids are common defects generated during manufacturing or prolonged services of composites. Depending on the local physical environment, microvoids may form as two types, namely, matrix voids and interfiber voids. These voids are known to have detrimental effects on the load bearing capacity of composites. However, it is relatively unknown the quantitative influence of these voids on the mechanical strength of composites. Without a direct mapping between defects and ply-level constitutive behavior, high-fidelity progressive failure predictions of composite structures is challenging. To bridge the gap, a micromechanics-based finite element framework is developed to investigate composites failure in the presence of three interfiber voids and the matrix void under transverse compression, tension, shearing, and longitudinal shearing. Mechanical strengths under these four loading modes are correlated with microstructural parameters including the void volume fraction, fiber-to-void number ratio, and void orientation. In general, at the same void volume fraction, the pentagonal interfiber void lowers strength the most, followed by the square interfiber void, the triangular interfiber void, and the circular matrix void. The weakening effect is strongly associated with stress concentration in the vicinity of voids, making the fiber-to-void number ratio an important parameter as it determines the local geometry. While void orientation shows limited influence, void size is found to play an important role. Results are expected to guide design and manufacturing of composite materials to achieve less critical flaws and higher strengths. Quantitative understanding of the criticality of voids of various configurations will also assist in-situ evaluation of composite materials.